PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIPA SMAN 1 PARIAMAN - Andika Putri Utami (Departemen Matematika, 2019)
Learning outcomes can measure students' abilities. However, in reality there were still many mathematics learning outcomes of students who were low or under passing grade, one of which occured in class XI MIPA students of SMAN 1 Pariaman. Discovery learning is one of learning models that can improve students mathematics learning outcomes. To increase the mathematics learning outcomes of students, it is necessary to analyze the mistakes made by students. Errors of students were analyzed and grouped by type of error according to Newman. This type of research was quasi-experiment and descriptive with a Randomized Control-Group Only Design study design. Based on the data analysis of the final test results that the mathematics learning outcomes of students who used the discovery learning model are better than conventional learning. Keywords – discovery learning, error according to Newman, mathematics learning outcomes.